Quantitative assessment of the 103-hexagon multifocal electroretinogram in detection of hydroxychloroquine retinal toxicity. Issue 5 (10th February 2012) - Adam, Murtaza K; Covert, Douglas J; Stepien, Kimberly E; Han, Dennis P
Abstract : Purpose: To evaluate the utility of ring ratios in detecting hydroxychloroquine (HCQ) related retinal toxicity using the 103-hexagon multifocal electroretinogram (mfERG). Design: Retrospective cross-sectional study. Methods: 23 patients taking HCQ were consecutively evaluated for retinal toxicity and divided into those without (HCQ-non-toxic group) and with documented visual field loss (HCQ-toxic group). A control patient group without retinal disease and not on HCQ was used for comparison. 103-hexagon P1 mfERG amplitude response densities were analysed by averaging the 103 responses into six (age-corrected) concentric rings (R1 –R6 ), calculating standard ring ratios (R1 :R2 –R1 :R6 ) and R5 ring ratios (R5 :R1 –R5 :R6 ). Receiver operating characteristic curves were used to compare these tests for detecting toxicity. Results: Relative to HCQ-non-toxic and control groups, the HCQ-toxic group showed generalised reduction of the 103-hexagon mfERG absolute responses most prominent in the foveal/pericentral regions. R5 ring ratios were superior to standard ring ratios in discriminating the HCQ-toxic from the HCQ-non-toxic and control groups and were approximately equivalent to pericentral absolute ring responses in detecting HCQ retinal toxicity by receiver operating characteristic criteria, with R5 :R4 and R5 :R3 ratios performing best. However, R5 ring ratios revealed improved sensitivity over absolute ring responses (89% vs 73%) at a 95% specificity threshold. Conclusions: Ring ratio analysis using the R5 ring response as the 'internal reference ring' appeared equivalent to pericentral absolute ring responses in detecting HCQ retinal toxicity, and possibly superior at clinically desirable specificity thresholds. R5 ring ratios did not require age correction, a potential clinical advantage over absolute ring responses.